Sociodemographic Characteristics, HIV-Related Risk Behaviors and HIV Prevalence of Vulnerable Men in Tehran, Iran - Mohraz, Minoo; SeyedAlinaghi, SeyedAhmad; Asadollahi-Amin, Ali; Golrokhi, Rahele; Khoei, Effat M.; Yousefi, Habib; Jafari, Fatemeh; Dadras, Omid (Current HIV Research, 2021)
Background: Sexual minorities, such as men who have sex with men (MSM), are disproportionately impacted by HIV/AIDS compared to heterosexual men. The increased prevalence of HIV/AIDs among this group of individuals is associated with increased participation in HIV-related risk behavior, such as multiple sexual partnerships and injection drug use. However, very little is known about the prevalence of HIV and the risk behaviors related to HIV infection among MSM in Iran. This absence of data is due to the increased discrimination and stigmatization MSM, and other vulnerable populations face in Iran. This study was conducted to identify HIV-related risks, HIV prevalence and sociodemographic characteristics of the MSM population in Iran. Methods: A cross-sectional study was conducted among MSM attending the Sexual Health Clinic at Imam Khomeini Hospital in 2018. A sexual health screening questionnaire was used to aid in identifying HIV-related risk behaviors. HIV status was determined using an HIV rapid test and confirmed by an ELISA. Results: One hundred MSM enrolled in this study, out of which 41% were 18-25 years old. The majorities were single; almost one-third had a diploma degree. Only a fifth were employed, and about a quarter (25%) reported substance abuse. Among eighty-three people (83%) reported having sex during the past three months, and only 27 (27.3%) of participants always used condoms for sex. Among 80 participants tested for HIV, two positive results were detected (2.5%). Conclusion: Data collected through a sexual health questionnaire indicated that the prevalence of HIV is increased among MSM in Iran. This finding sheds light on the urgent need for the implementation of social programs providing counseling and healthcare to vulnerable populations in Iran.
Keywords: key population